36 Outcomes of incidentally detected ovarian cancers diagnosed at time of risk-reducing salpingo-oophorectomy in brca mutation carriers. (18th September 2019) - Cowan, R; Pedra Nobre, S; Zhou, Q; Iasonos, A; Long Roche, K; Gardner, G; Abu-Rustum, N; Aghajanian, C; Cadoo, K
Abstract : Objectives: It has been suggested that women with BRCA mutation and incidentally detected occult invasive ovarian cancer (OOC) diagnosed at the time of risk-reducing salpingo-oophorectomy (RRSO) have poorer prognosis than would be expected per stage. We sought to evaluate the prevalence and clinical outcomes of BRCA -mutated patients with OOC undergoing RRSO in a tertiary referral center. Methods: Patients with a BRCA mutation who underwent RRSO from 01/2005–05/2017 were identified, and records reviewed. Women with preoperative suspicion for malignancy (e.g. adnexal mass or elevated CA125) were excluded. Results: 532 patients with BRCA mutation undergoing RRSO were identified. 26 (4.8%) had OOC. Median age was 55 years (range 42–75). 15(58%) patients had BRCA1, 9(34%) BRCA2, and 2(8%) had a mutation in both genes. All OOCs were high-grade serous: 10 (38%) Stage I, 8 (31%) Stage II, 8(31%) Stage III. 24(92%) patients received adjuvant platinum/taxane therapy. Of Stage III patients, 4 (50%) had microscopic disease only, 4 (50%) had suspicious intraoperative findings. At a median follow-up of 53.6 mos (7–164) no Stage I patients have recurred; 1(13%) Stage II patient and 5(63%) Stage III patients have recurred. Five-year PFS was 74% (95%CI 44–87.7%); median PFS for the cohort was 129 months (35.9-not estimable). Five-year DSS was 96.2% (95%CI 73.9–99.4%), median DSS not reached. Conclusions: Consistent with prior reports, almost 5% of patients had OOC detected at time of RRSO. In contrast to prior data, the majority had early-stage disease with excellent PFS and DSS outcomes as would be expected per stage.